﻿
Question
Thu February 10, 2011 By: Sneha George

# If the p th term of an AP is a and q th term is b then show that the sum of its first (p+q) terms is p+q/2[a+b+a-b/p+q][2p+1].

Thu February 10, 2011
Dear student,

Let 'Î±' be the first term, and 'd' the common difference of the A.P..

Then,

T(n) = Î± + (n-1)d

S(n) = (n/2) [ 2Î± + (n-1) d ] ................. (1)

Now, given that : T(p) = a and T(q) = b.

â´ Î± + (p-1)d = a .......... (2)

Î± + (q-1)d = b .......... (3)

Subtracting (3) from (2),

(p-q)d = (a-b)

â´ d = (a-b) / (p-q) ....................... (4)

2Î± + (p+q-2)d = a + b

â´ [ 2Î± + (p+q-1)d ] - d = a + b

â´ [ 2Î± + (p+q-1)d ] = (a+b) + d

â´ from (4),

[ 2Î± + (p+q-1)d ] = (a+b) + (a-b)/(p-q) .......... (5)

Putting n = (p+q) in(1), and then using (5),

S(p+q) = [ (p+q)/2 ]Â· [ 2Î± + (p+q-1)d ]

= [ (p+q)/2 ]Â· [ (a+b) + (a-b)/(p-q) ]

We hope that clarifies your query.

Regards,

Team

TopperLearning

Related Questions
Fri February 17, 2017

# The  19th term of an A. P.  is equal to three times its sixth term. If its 9th term is 19, find the A.P.

Mon February 13, 2017

﻿